Combined Targeted Proteomics and Oxylipin Metabolomics for Monitoring of the COX‐2 Pathway. Issue 3 (28th September 2020) - Hartung, Nicole M.; Ostermann, Annika I.; Immenschuh, Stephan; Schebb, Nils Helge
Abstract: The important role of inducible cyclooxygenase‐2 (COX‐2) in several diseases necessitates analytical tools enabling thorough understanding of its modulation. Analysis of a comprehensive oxylipin pattern provides detailed information about changes in enzyme activities. In order to simultaneously monitor gene expression levels, a targeted proteomics method for human COX‐2 is developed. With limits of detection and quantification down to 0.25 and 0.5 fmol (on column) the method enables sensitive quantitative analysis via LC‐MS/MS within a linear range up to 2.5 pmol. Three housekeeping proteins are included in the method for data normalization. A tiered approach for method development comprised of in silico and experimental steps is described for choosing unique peptides and selective and sensitive SRM transitions while avoiding isobaric interferences. This method combined with a well‐established targeted oxylipin metabolomics method allows to investigate the role of COX‐2 in the human colon carcinoma cell lines HCT‐116, HT‐29, and HCA‐7. Moreover, the developed methodology is used to demonstrate the time‐dependent prostanoid formation and COX‐2 enzyme synthesis in lipopolysaccharide‐stimulated human primary macrophages. The described approach is a helpful tool which will be further used as standard operation procedure, ultimately aiming at comprehensive targeted proteomics/oxylipin metabolomics strategies to examine the entire arachidonic acid cascade.